Ethnobotanical importance and conservation status of Citrullus colocynthis (L.) Schrad in division Mirpur, Kashmir Himalaya. - Mazher, Mubsher; Ishtiaq, Muhammad; Hamid, Bilqeesa; Marifatul Haq, Shiekh; Mazhar, Mussaddaq; Bashir, Faiza; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2023)
Background: Citrullus colocynthis (L.) Schrad has been used traditionally for curing ailments in humans and animals in different parts of the world. The current study was conducted to determine the ethnobotanical importance of C. colocynthis in division Mirpur, Kashmir Himalaya. Methods: Twelve well-planned ethnobotanical surveys of the study area were arranged. A total of 118 respondents of varying educational backgrounds, professional affiliations, and age groups were interviewed. Visual appraisal assessment (VAA) and rapid rural appraisal (RRA) methods were used to collect the qualitative and quantitative data. Results: The plant part value (PPV) indicated that fruit as a whole (PPV=90) and its parts, i.e., rind (PPV=83.33), pulp (PPV=80), and seeds (PPV=90) are mostly used for ethnomedicinal purposes. C. colocynthis was found to be most commonly used to treat microbial infections (FL=0.91), diabetes (FL=0.86) and obesity (FL=0.84). The informant agreement ratio (IAR) values indicate that C. colocynthis has antidiabetic (IAR=0.96), antilipidemic (IAR=0.91), and antimicrobial (IAR=0.88) potential. The conservation status was calculated to be 1.82, and it was stated that C. colocynthis is vulnerable in the study area. Conclusion: It can be concluded that C. colocynthis has been an important ethnomedicinal plant in the study area. It is still in use by farmers, herbalists, nomadic people, and rural people for the treatment of microbial infections, obesity, constipation, and blood purification. Due to its unchecked utilization, there is severe pressure on its survival, and its conservation is needed immediately. Keywords: Traditional Ethnomedicines, Mirpur, Conservation Status, Citrullus colocynthis